2009
DOI: 10.1002/ejic.200900815
|View full text |Cite
|
Sign up to set email alerts
|

A Pentanuclear Cu/Co/Ni Complex with 2‐(Dimethylamino)ethanol – Observation of a Rare Molecular Structure Type and Its Place in General Structural Types: An Analysis of the Cambridge Structural Database

Abstract: Heterotrimetallic complex [CuII2CoIINiII2(Me2Ea)5Cl5(H2O)]·CH3CN·H2O has been prepared in a one‐pot reaction of zero‐valent copper with cobalt and nickel chlorides in an acetonitrile solution of 2‐(dimethylamino)ethanol (HMe2Ea) in the open air. The metal stoichiometry obtained by atomic absorption analysis was further confirmed by single‐crystal X‐ray diffraction investigations. The pentanuclear molecule is formed by a previously unknown combination of incomplete cube M3(μ3‐X)(μ‐X)3 and triangle bipyramidal M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Although this concept was not used in our investigations, the idea of MSTs was found to be appealing to compare the structures of related compounds. The study of the statistical distribution of MSTs35 within the Cambridge Structural Database46 revealed some widespread and rare MSTs of different nuclearities, allowing the coordination cores of novel complexes to be classified according to their rarity. Clearly, the prevalence of the MSTs depends on the topology.…”
Section: Molecular Structure Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this concept was not used in our investigations, the idea of MSTs was found to be appealing to compare the structures of related compounds. The study of the statistical distribution of MSTs35 within the Cambridge Structural Database46 revealed some widespread and rare MSTs of different nuclearities, allowing the coordination cores of novel complexes to be classified according to their rarity. Clearly, the prevalence of the MSTs depends on the topology.…”
Section: Molecular Structure Typesmentioning
confidence: 99%
“…Screening of the reaction system Cu 0 + CoCl 2 + NiCl 2 + HMe 2 Ea revealed that complex 30 can be obtained with a Cu/Co/Ni ratio close to 2:1:2. When a ratio of 1:1:1 was used, the heterotrimetallic complex 31 with a different structure35 was obtained [reaction (38)].…”
Section: Complexes Of Pentanuclear Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The pentanuclear aminoalkoxide complex [Cu II 2 Co II Ni II 2 (Me 2 NC 2 H 5 O) 5 Cl 5 (H 2 O)] has been prepared in a one-pot reaction of zero-valent copper with cobalt and nickel chlorides and has a zigzag arrangement of metal centres within one molecule formed by incomplete cube fragments joined by common faces. 14…”
Section: Nickelmentioning
confidence: 99%